Developing of Palembang-Local-Culture Narrative Reading Materials for the Eleventh Grade of Senior High School - Silvia Indri Triani; Eryansyah Eryansyah; Margaretha Dinar Sitinjak (STAI Hubbulwathan Duri, 2022)
The objectives of this study were to find out the validity, practicality, and potential effect of the developed Palembang-local-culture narrative reading materials about Palembang food. This study was designed as research and development involving three phases including analysis, design, and evaluation and revision phases. The formative evaluation was done through one-to-one evaluation, small group evaluation, and field trial. The subjects of this study were eleventh grade of senior high school in Palembang. The validity was done in expert review. The validity score of the developed product was 3,20 which was categorized as high validity level. The practicality was conducted in one-to-one and small group evaluation. The practicality of one-to-one evaluation was 3,6 which was at very high practical level and the practicality in small group evaluation was 3,7 which was at very high practical level. The result in field trial was categorized as effective. It showed that there were 18 students (78,26%) out of 23 students in field trial reached the MMC (Minimum Mastery Criterion) which was 75.